(untitled) (Symposium on Natural and Applied Sciences, 2026)
This paper explores how contemporary detective fiction transforms the detective protagonist into a figure of existential uncertainty. Through a comparative reading of Nuriddin Ismoilov’s “O’limga mahkum qilinganlar” and “Tana French’s In the Woods”, the study argues that the modern detective is no longer presented only as an investigator who solves a criminal case. Instead, the protagonist becomes a character whose work exposes a deeper crisis of identity, memory, loyalty, and moral responsibility. In Ismoilov’s novel, Sobir exists inside a dangerous world of secret service, disguise, and constant vigilance, and this environment makes identity appear unstable but ethically necessary. In French’s novel, the detective is shaped by memory, trauma, and the pressure of an unresolved past, so the investigation becomes a personal search for meaning as much as a professional task. The comparison shows that detective fiction in the contemporary period often uses crime narratives to examine the fragile relation between outward roles and inward selfhood.